A human and a plant intron-containing tRNATyr gene are both transcribed in a HeLa cell extract but spliced along different pathways. - van Tol, H (1987)
tRNA splicing enzymes had been identified in mammalian and plant cells long before homologous intron-containing tRNA genes were detected. The tRNATyr gene presented here is the first intron-containing, human tRNA gene for which transcription and pre-tRNA maturation has been studied in a homologous system. This gene is disrupted by a 20-bp long intron and encodes one of the two major human tRNAsTyr which have been purified and sequenced. A tRNATyr gene recently isolated from Nicotiana also contains an intron and codes for a functional, major cytoplasmic tRNATyr. Both tRNA genes are efficiently transcribed in a HeLa cell nuclear extract. Each of them produces two independent primary transcripts because of two initiation and termination sites, respectively. The maturation of the tRNATyr precursors proceeds along different pathways. The intervening sequence of the human pre-tRNATyr is excised first, followed by ligation of the tRNA halves and maturation of the flanks, as has been shown for all intron-containing tRNA genes transcribed in HeLa extract. The order of maturation steps is reversed for the plant pre-tRNATyr: processing of the flanking sequences precedes intron excision. This maturation pathway corresponds to that observed in vivo for tRNA biosynthesis in Xenopus oocytes and yeast.